ANALYSIS OF FINANCIAL STATEMENTS AT TIRTA DUMAI BERSEMAI DRINKING WATER COMPANY (PDAM TIRTA DUMAI BERSEMAI) - Rispa Eliza; Putri Haizah Sakilah; Fitria Sari Ayu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Meeting the needs of the Dumai city community in getting clean water, the Tirta Dumai Bersemai Drinking Water Company is here to make the best service efforts in distributing clean water to the Dumai City area. The Regional Drinking Water Company (PDAM) is one of the regional-owned business units, which is engaged in the distribution of clean water for the general public. expanding the area and increasing the productivity of the company's waterworthiness did not escape the assistance of investors and other related parties. Key financial reports of all collaborations with various parties to the Tirta Dumai Bersemai Drinking Water Company. Analysis of financial statements can be material or evidence of consideration whether the company is in good or bad condition, healthy or unhealthy. This study aims to look at the condition and performance of the Tirta Dumai Bersemai Regional Water Company with data processing methods with financial ratios and find the results that overall the company is in a safe or good condition for investment from various investors, and has good company performance in running its business.